(untitled) (Global Journal of Science Frontier Research, 2013)
This study examined kitchen resource, reasoning ability level, academic performance and retention of SS2 Chemistry students in Thermo-chemistry. Thermochemical activities in the kitchen such as, fermentation of samples of five different juices (mango, orange, pineapple, grape and paw-paw), heating capacities of five samples of wood (mango, orange, guava, almond and rubber), induced thermal decomposition of five samples of shellfish shells powder (mangrove snail shell, fresh water periwinkle shell, freshwater snail shell, clam shell and mangrove periwinkle shell) and dissolution of five samples of glucose (2g, 4g 6g, 8g and 10g) were used for the study. The sample comprised 240 drawn from four secondary schools in Calabar Education Zone of Cross River State of Nigeria. Quasi experimental factorial research design was used for this study. Chemistry Achievement Test (Cat), Chemistry Retention Test (Cat), and Reasoning Ability Test (Rat) were used for data collection. Analysis of covariance (ANCOVA) was used in the analysis of data. From the findings, the use of kitchen resources enhanced the performance and retention level of high and low reasoning ability level of students exposed to kitchen resources during the teaching of Thermochemistry. It was recommended that teachers should be encouraged to adopt kitchen resources in science teaching.